Transient unilateral brachial plexus block following landmark-guided superficial cervical plexus block: A case report - Isabel Besozzi; Andrea Goldmann; Daniel Button; Stefanie Senn; Caveh Madjdpour (SAGE Open Medical Case Reports)
We report a case of a 61-year-old male patient with impaired function of the contralateral brachial plexus after right parathyroidectomy. The symptoms appeared directly after emerging from general anaesthesia and disappeared completely within 24 h after surgery. The follow-up check after 6 weeks was unremarkable. The patient suffered from asthma, osteoporotic degenerative changes of the spine and a chronic impingement of the left shoulder. He showed no signs of pain or limitations while reclining his neck during pre-operative airway assessment. Before surgery, a bilateral superficial cervical plexus block was performed by the surgeon using the landmark technique. We discuss the positioning of the neck and cervical spine in preparation for surgery and pre-operative superficial cervical plexus block as possible causes for the impaired function of the brachial plexus observed in this patient. We conclude that the latter was the most likely cause in this patient and recommend considering ultrasound guidance for the performance of superficial cervical plexus block.